Landless entrepreneurs: Neoliberalism, reform and peasant struggle in Palmar Sur, Osa - Guillén Araya, María José (2020)
This article is one of the outcomes of an action-research process with peasant organizations in Palmar Sur, Osa; privileging the experience of struggle of these organizations, I analyze the institutional transformation of the Agrarian Development Institute into the Rural Development Institute, and its land distribution policy. The neoliberal approach of the policy is evident in the findings of this research: the reform promotes the production of an entrepreneurial subjectivity, while consolidating a process of dispossession in which peasants are separated from the land. The state regulates the access to this means of production no longer through ceding property deeds but by controlling the economic conduct of the so-called "beneficiaries" of the public policy.